A dynamic model of global natural gas supply. (15th May 2018) - Crow, Daniel J.G.; Giarola, Sara; Hawkes, Adam D.
Highlights: A new simulation model of global (28 regions) upstream gas supply is presented. Builds supply curves from field breakeven prices using extensive industrial data. The spatial resolution is individual gas fields; the temporal resolution is yearly. Realistic investment and operating decisions in response to price & demand signals. A validation is performed using the US Shale gas boom as a historic case study. Abstract: This paper presents the Dynamic Upstream Gas Model (DYNAAMO); a new, global, bottom-up model of natural gas supply. In contrast to most "static" supply-side models, which bracket resources by average cost, DYNAAMO creates a range of dynamic outputs by simulating investment and operating decisions in the upstream gas industry triggered in response to investors' expectations of future gas prices. Industrial data from thousands of gas fields is analysed and used to build production and expenditure profiles which drive the economics of supply at field level. Using these profiles, a novel methodology for estimating supply curves is developed which incorporates the size, age and operating environment of gas fields, and treats explicitly the fiscal, abandonment, exploration and emissions costs of production. The model is validated using the US shale gas boom in the 2000s as a historic case study. It is found that the modelled market share of supply by field environment replicates the observed trend during the period 2000–2010, and that the model price response during the same period – due to lower capacity margins and the financing of new projects – is consistent with market behaviour.